2009
DOI: 10.1007/s12229-009-9027-y
|View full text |Cite
|
Sign up to set email alerts
|

Premature Decline of Eucalyptus and Altered Ecosystem Processes in the Absence of Fire in Some Australian Forests

Abstract: We propose a model of 'premature tree decline' whereby an absence of fire hastens the mortality of overstorey eucalypts in some forests. This model is relevant to some temperate Australian forests in which fire regimes have shifted from relatively frequent before European settlement to infrequent following settlement. The increased development of midstorey vegetation and litter accumulation has occurred since European settlement in some specific examples of Australian forests and woodlands. Our model proposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…Fire is typically an agent of change that alters the structure of woodlands (Penn et al 2003;Greenberg and Waldrop 2008;Close et al 2009), assists with the regeneration of trees and shrubs by enhancing seed release and establishment (Burrows et al 1990;Mercer 1994), and can stimulate flowering in many tree species (Pyke 1983;Lamont and Downes 2011;Shepherd et al 2011). Mass recruitment of eucalypts can 465 occur after fire events (Wellington and Noble 1985;Ruthrof et al 2003).…”
Section: Reproductive Effort and Time Since Last Firementioning
confidence: 99%
“…Fire is typically an agent of change that alters the structure of woodlands (Penn et al 2003;Greenberg and Waldrop 2008;Close et al 2009), assists with the regeneration of trees and shrubs by enhancing seed release and establishment (Burrows et al 1990;Mercer 1994), and can stimulate flowering in many tree species (Pyke 1983;Lamont and Downes 2011;Shepherd et al 2011). Mass recruitment of eucalypts can 465 occur after fire events (Wellington and Noble 1985;Ruthrof et al 2003).…”
Section: Reproductive Effort and Time Since Last Firementioning
confidence: 99%
“…Declining stands often develop dense understoreys of a few native or exotic shrubs and decline has sometimes been attributed to reduced water and nutrient status as a result of competition from these "invasive" understoreys [5,6]. However several studies have shown that soil water and nitrogen status is increased in declining stands, and trials of understorey removal have failed to ameliorate declines [7].…”
Section: Invasions In Eucalypt Systemsmentioning
confidence: 99%
“…Exclusion of frequent mild fires is a disturbance that favours fire-sensitive, shade-tolerant, nutrient-loving "invaders" over intolerant, fire-demanding eucalypts adapted to infertile soils [4]. Susceptible eucalypt ecosystems are associated with sheltered sites on infertile, poorly buffered and poorly drained soils where shade and adverse soil conditions develop quickly in the absence of fire [5,8].…”
Section: Traits Of Successful "Invaders" and Properties Of Susceptiblmentioning
confidence: 99%
“…Disturbances such as grazing, timber harvesting and limestone quarrying (McArthur and Bartle 1980;Keighery 2002) have impacted on ecosystem function and may have contributed to E. gomphocephala decline. A range of biotic and abiotic factors including boring insects (Fox and Curry 1980;Fox 1981), foliar and canker pathogens (Taylor et al 2009), changes in the soil bacterial functional diversity (Cai et al 2010), changes to fire regimes (Archibald et al 2005;Archibald 2006;Close et al 2009;Archibald et al 2010) and hydrology (Drake 2008), have been associated with E. gomphocephala decline, but causal relationships have not been established. The progressive canopy thinning and diebacks typical of some Phytophthoraassociated tree declines (Shearer and Tippett 1989;Hansen and Delatour 1999;Brasier et al 2003) suggest that Phytophthora species may also contribute to E. gomphocephala decline.…”
Section: Introductionmentioning
confidence: 99%
“…Stem injections of other chemicals with known biological effects, such as mineral nutrients and insecticides, may help to clarify the involvement of some abiotic and biotic factors in tree decline. Eslick (2005) and Close et al (2009;2011) have identified zinc deficiency as a factor associated with E. gomphocephala decline. South-western Australia is an ancient, semi-arid land with a diverse native flora long adapted to the nutrient poor soils.…”
Section: Introductionmentioning
confidence: 99%